MORALITAS UNDANG-UNDANG: KAJIAN FILOSOFIS TERHADAP UNDANG-UNDANG NOMOR 17 TAHUN 2014 TENTANG MPR, DPR, DPD DAN DPRD (MD3) - Kuswanto Kusnadi (Refleksi Hukum: Jurnal Ilmu Hukum, 2019)
This article represents a legal philosophy study which applies philosophical approach while undertaking juridical analysis over the legal drafting of Law No. 17 of 2014 on the People’s Consultative Assembly, the People’s Representative Council, and the Regional Representatives Council. This article discovers a problem regarding on the moral commitment of the legal drafters of the Law. Ideally, the moral commitment requires the legal drafters to be cautious about the possibility of conflict of interest while drafting the Law. Unfortunately, Law No. 17 of 2014 does not represent the moral commitment, meaning it has failed the morality test to be called as law. This article also argues that legislation shall be justified by morality. If the law maker is unable to meet the precondition, the legislation will be labeled as an unjust law.